EFFECT OF ALKALI TREATMENT ON THE TENSILE STRENGTH OF LIDAH MERTUA FIBER/ POLYPROPYLENE RECYCLED BIOCOMPOSITE - Lokantara, I Putu; Suardana, NPG; Surata, IW; Winaya, INS (International Journal of Engineering and Emerging Technology, 2020)
The purpose of this study was to determine the effect of alkali fiber treatment on the tensile strength of composites. The material in this study was recycled polypropylene from plastic beverage glass and lidah mertua fiber with a fiber length of 180 mm, fiber treatment using 5% NaOH and without treatment. Composite specimens were prepared using the hot press method at 170 o C for 120 minutes. Tensile testing with the dimensions of the test specimen refers to ASTM D-638. The results of the test carried out the maximum tensile strength value of 71,606 MPa in fiber with 5% alkali treatment. The tensile strength of composites with alkali treatment increased 223% compared to the tensile strength without alkali